2014
DOI: 10.1037/a0035961
|View full text |Cite
|
Sign up to set email alerts
|

First saccadic eye movement reveals persistent attentional guidance by implicit learning.

Abstract: Implicit learning about where a visual search target is likely to appear often speeds up search. However, whether implicit learning guides spatial attention or affects post-search decisional processes remains controversial. Using eye tracking, this study provides compelling evidence that implicit learning guides attention. In a training phase, participants often found the target in a high-frequency, “rich” quadrant of the display. When subsequently tested in a phase during which the target was randomly located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
80
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 61 publications
7
80
1
Order By: Relevance
“…However, the removal of regularities alone was not sufficient to weaken the attentional bias to the initial regularities (Experiment 2), and in fact the bias was equally strong in both halves of exposure. This persistence effect is consistent with previous studies on probabilistic cueing which showed that attention was persistently drawn to a spatial location in which targets were initially more likely to appear (Jiang et al, 2013;Jiang et al, 2014). The removal of the initial regularities coupled with the addition of new regularities reduced the attentional bias, but the bias had not reversed.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, the removal of regularities alone was not sufficient to weaken the attentional bias to the initial regularities (Experiment 2), and in fact the bias was equally strong in both halves of exposure. This persistence effect is consistent with previous studies on probabilistic cueing which showed that attention was persistently drawn to a spatial location in which targets were initially more likely to appear (Jiang et al, 2013;Jiang et al, 2014). The removal of the initial regularities coupled with the addition of new regularities reduced the attentional bias, but the bias had not reversed.…”
Section: Discussionsupporting
confidence: 81%
“…The initial exposure to regularities can prioritize the processing of the regularities (Zhao et al, 2013), even when the regularities are no longer present (Jiang et al, 2013;Jiang, Won, & Swallow, 2014). In a probabilistic cueing study, participants detected a target which was more likely to appear in one quadrant (rich quadrant) than in other quadrants (sparse quadrants), and the detection was faster when the target appeared in the rich quadrant than in the sparse quadrants (Jiang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Probability cuing in visual search tasks is coded in a head-centered reference frame, does not update with movements through space, and increases the number of first saccades to the rich region (Jiang & Swallow, 2013b; Jiang, Won, & Swallow, 2014). In addition, it appears to operate in a manner that is qualitatively different from goal-driven or explicit attentional biases (Jiang, Swallow, & Rosenbaum, 2013; Jiang, Swallow, & Sun, 2014; Jiang, Won, & Swallow, 2014). We have taken these findings to suggest that probability cuing influences how attention moves through space, by increasing the likelihood that it moves in a certain direction.…”
Section: Discussionmentioning
confidence: 99%
“…The priority weights are determined by top-down factors, such as the observer's explicit goal, and bottom-up factors, such as perceptual saliency (Desimone & Duncan, 1995; Egeth & Yantis, 1997; Wolfe, 2007). In addition, one's past experience often guides spatial attention (Awh, Belopolsky, & Theeuwes, 2012; Chun, 2000; Hutchinson & Turk-Browne, 2012; Jiang, Swallow, Rosenbaum, & Herzig, 2013; Jiang, Won, & Swallow, 2014). Yet, unlike an explicit goal or perceptual saliency, previous experience includes a possibly infinite amount of information.…”
mentioning
confidence: 99%
“…Attention and gaze can then be shifted to the location containing the most relevant information (e.g., highest attentional weight) for the current task (Wischnewski et al, 2010; Schneider, 2013). Alternatively, task-related memory can be used to shift attention and gaze directly to a retrieved target position without the need to process visual features (Foerster et al, 2011, 2012, Jiang et al, 2013, 2014). Especially, when performing well-known sensorimotor actions, strong memory codes are used to direct attention and gaze in a task-dependent manner (Foerster et al, 2011, 2012).…”
Section: Discussionmentioning
confidence: 99%